Correction to: Broad-scale distribution of marine benthic litter in shallow waters along the Turkish Aegean coast: a SCUBA-based assessment - Yaşar Özvarol; Barış Akçalı; Erhan Mutlu (Environmental Science and Pollution Research, 2026)

Ecological comparison of non-indigenous with indigenous megabenthic crustaceans in an oligotrophic eastern Mediterranean gulf - Erhan Mutlu; Annalisa Patania (Regional Studies in Marine Science, 2026)

Comparison of population dynamics parameters estimated for 34 bony fishes in oligotrophic Mediterranean shelf/break waters - Erhan Mutlu; Claudia Miglietta; Ilaria de Meo; Mehmet Cengiz Deval (Journal of Fish Biology, 2026)
Understanding the life‐history patterns of fish species is crucial for effective fisheries management across temporal and spatial scales. This study investigates the population dynamics of fish inhabiting the shelf and break zone of the Gulf of Antalya, a highly oligotrophic region of the Mediterranean Sea that serves as a major spawning ground for various species, including fast‐growing deep‐sea fishes that reach maturity within 1–2 years. Population parameters, such as asymptotic length and growth rate, were estimated from length–frequency distributions using ELEFAN I in the FISAT programme. Multi‐species analyses, particularly of dominant taxa, were performed to evaluate their interactions within the study area, while seasonality and environmental variability were also considered. A total of 165 demersal and some pelagic fish species were recorded throughout the year, of which 34 bony fish species were examined in detail. The results showed that population parameters varied significantly with both fish size and bottom depth. Along the shelf (10–75 m), asymptotic length ( L ∞ ) and growth rate ( K ) decreased with depth. At the shelf edge (200 m), L ∞ remained high and K declined, whereas at the shelf break (300 m), L ∞ decreased and K increased. Mortality rates [total mortality ( Z ) and natural mortality ( M )] declined with increasing fish size, with medium‐sized fishes exhibiting the highest Z values. The relationship between maximum age ( t max) and natural mortality ( M ) showed a significant correlation, particularly across size classes rather than depth strata. A comparative analysis with data from 524 publications indicated that population parameters are strongly influenced by geographical location within the Mediterranean, temporal variation (e.g., pre‐2000s, 1990s–2000s, post‐2000s) and west–east spatial gradients. This study also provides the first comprehensive population characteristics for four species – Epinephelus aeneus , Glossanodon leioglossus , Macroramphosus scolopax and Pagrus caeruleostictus – with important ecological and management implications.

Broad-scale distribution of marine benthic litter in shallow waters along the Turkish Aegean coast: a SCUBA-based assessment - Yaşar Özvarol; Barış Akçalı; Erhan Mutlu (Environmental Science and Pollution Research, 2026)
Purpose Marine litter, particularly benthic macro debris, poses persistent ecological and socio-economic threats to Mediterranean seafloor ecosystems. This study addresses critical knowledge gaps in the spatial distribution, composition, and accumulation characteristics of benthic litter along the understudied Turkish Aegean coastline. Methods We conducted the first large-scale, depth-stratified SCUBA-assisted assessment of benthic macro litter across 326 stations along approximately 1600 km of the Turkish Aegean coast. Surveys were performed at six discrete depth levels (5–30 m) following MSFD and UNEP/MAP protocols. Litter items were classified into nine standardized material categories, and both abundance (n km −2 ) and mass (kg km −2 ) metrics were quantified. Multivariate statistical analyses (PCA and PERMANOVA) were applied to examine spatial and depth-related patterns in litter distribution. Results A total of 822 litter items (4147 kg) were recorded, corresponding to mean values of 77.4 n km −2 and 383 kg km −2 . Plastics dominated numerical abundance but contributed relatively little to total mass, whereas metal and concrete debris accounted for a disproportionate share of mass. Shallow stations (5–10 m) were characterized by higher abundances of lightweight litter associated with nearshore activities, while deeper stations more frequently contained heavier debris linked to maritime and aquaculture-related operations. Spatial variability in litter accumulation was primarily associated with material composition and localized human activities rather than broad administrative divisions. Conclusion This study provides the first harmonized and policy-relevant baseline for benthic litter along the Turkish Aegean coast. The findings highlight the importance of integrating mass-based indicators alongside abundance metrics to better assess ecological risk and inform management strategies. SCUBA-assisted surveys are shown to be a robust and complementary approach for monitoring benthic litter in shallow, heterogeneous coastal environments within MSFD/UNEP-aligned frameworks.

Summer Surface Phytoplankton Assemblages along Physically Discrete Water Masses of the Entire Turkish Mediterranean Coast - Doğukan Karaca; Erhan Mutlu; Zahit Uysal (Thalassas: An International Journal of Marine Sciences, 2026)

A Broad-Scale Summer Spatial Structure of Pelagic Fish Schools as Acoustically Assessed Along the Turkish Aegean Coast - Erhan Mutlu (Journal of Marine Science and Engineering, 2025)
Fish stocks and their management are paramount for sustainable fisheries under the ongoing changes in atmosphere–sea interactions. The Aegean Sea, one of the composite seas influenced by different water masses, is characterized by a diverse ecosystem. Small pelagic fish are abundant and tend to form schools that vary in size. One of the most efficient and rapid techniques for sampling fish schools over a large area is the use of acoustic methods. Therefore, an acoustic survey was conducted in the coastal areas along the entire Turkish Aegean waters between June and August 2024, using a scientific quantitative echosounder equipped with a split-beam transducer operating at 206 kHz. During the survey, environmental parameters, including water physics, optics, and bathymetry, were measured at 321 stations. Additionally, satellite data were used to obtain water primary production levels for each sampling month across the entire study area. Using a custom computer algorithm written during the present study in MATLAB (2021a), fish schools were automatically detected to measure various morphological and acoustic features. Through a series of statistical analyses, three optimal clusters, validated with the total silhouette sum of distances (1317.38), were identified, each characterized by specific morphological, acoustic, and environmental variables associated with different areas of the study. School morphology and acoustic properties also varied with bottom depth. Cluster 1 was mostly found in open and relatively deep waters. Cluster 2 appeared in areas impacted by anthropogenic sources. Principal Component Analysis (PCA) revealed that the first component (PCA1) was correlated with school height from the bottom (HFB) and overall school height (SH), followed by minimum depth (MnD), maximum depth (MxD), and volume backscattering strength at the school edge (SvE). The second component (PCA2) was associated with school width (SW) and area (A). Cluster 1 was characterized by schools with large SW and A, and relatively high HFB and SH. Cluster 2 showed low HFB and SH, while Cluster 3 had high MnD and MxD and low SvE. Based on the descriptors for these clusters, each cluster could be attributed to fish species at different life stages inferred based on target strength (TS), namely sardine, horse mackerel, and chub mackerel, distributed along the entire Turkish Aegean coast.

Ecological Comparison Between Commercial and Discard Fish in the Antalya Gulf, Eastern Mediterranean - Erhan Mutlu; Ilaria de Meo; Claudia Miglietta; Mehmet Cengiz Deval (Thalassas: An International Journal of Marine Sciences, 2025)

Selective and sensitive molecularly imprinted polymer-based electrochemical sensor for detection of deltamethrin - Esma Mutlu; Ahmet Şenocak; Erhan Demirbaş; Atıf Koca; Duygu Akyüz (Food Chemistry, 2025)

Spatio-temporal density of the demersal Chondrichthyes assemblage in an upper bathyal of the eastern Mediterranean Sea - Mehmet Cengiz Deval; Erhan Mutlu (Marine Biodiversity, 2024)

A Broad-scale Biometrical Response of Pristine Posidonia Oceanica Meadow to Winter and Summer Conditions in the North-eastern Mediterranean Coast - Erhan Mutlu; Güler Sıla Duman; Doğukan Karaca; Yaşar Özvarol; Ahmet Şahin (Thalassas: An International Journal of Marine Sciences, 2024)

Density-depended Acoustical Identification of Two Common Seaweeds (Posidonia Oceanica and Cymodocea Nodosa) in the Mediterranean Sea - Erhan Mutlu; Cansu Olguner (Thalassas: An International Journal of Marine Sciences, 2023)

A Package of Script Codes, POSIBIOM for Vegetation Acoustics: POSIdonia BIOMass - Erhan Mutlu (Journal of Marine Science and Engineering, 2023)
Macrophytes and seagrasses play a crucial role in a variety of functions in marine ecosystems and respond in a synchronized manner to a changing climate and the subsequent ecological status. The monitoring of seagrasses is one of the most important issues in the marine environment. One rapidly emerging monitoring technique is the use of acoustics, which has advantages compared to other remote sensing techniques. The acoustic method alone is ambiguous regarding the identities of backscatterers. Therefore, a computer program package was developed to identify and estimate the leaf biometrics (leaf length and biomass) of one of the most common seagrasses, Posidonia oceanica. Some problems in the acoustic data were resolved in order to obtain estimates related to problems with vegetation as well as fisheries and plankton acoustics. One of the problems was the “lost” bottom that occurred during the data collection and postprocessing due to the presence of acoustic noise, reverberation, interferences and intense scatterers, such as fish shoals. Another problem to be eliminated was the occurrence of near-bottom echoes belonging to submerged vegetation, such as seagrasses, followed by spurious echoes during the survey. The last one was the recognition of the seagrass to estimate the leaf length and biomass, the calibration of the sheaths/vertical rhizomes of the seagrass and the establishment of relationships between the acoustic units and biometrics. As a result, an autonomous package of code written in MATLAB was developed to perform all the processes, named “POSIBIOM”, an acronym for POSIdonia BIOMass. This study presents the algorithms, methodology, acoustic–biometric relationship and mapping of biometrics for the first time, and discusses the advantages and disadvantages of the package compared to the software dedicated to the bottom types, habitat and vegetation acoustics. Future studies are recommended to improve the package.

Spatial geochemical structure of soft sediment on shallow littoral of the Gulf of Antalya, the eastern Mediterranean Sea - Mustafa Gürhan Yalçın; Erhan Mutlu; Cansu Olguner; Özge Özer Atakoğlu; Levent Bat; Ebru Yeşim Özkan (Marine Pollution Bulletin, 2023)

Expression of genes related to iron homeostasis in breast cancer - Tuba Mutlu; Emre Ozoran; Didem Can Trabulus; Canan Kelten Talu; Duygu Erhan; Meltem Mete; Mehmet Guven (Molecular Biology Reports, 2023)

Acoustic scattering properties of seagrass: In/ex-situ measurements of Posidonia oceanica - Erhan MUTLU; Cansu Olguner (Mediterranean Marine Science, 2023)
The marine prairies are paramount to the marine ecosystem playing a crucial role in various ways. Owing to the global atmospheric events inducing hydrospheric changes, marine seaweeds have been negatively affected and are vulnerable. Conventional methods (SCUBA), which were previously used to collect seagrasses, have become a destructive method for deriving unrecoverable damages for their stocks and have been replaced with remote sensing methods. Considering the advantages of the acoustic methods, two different in/ex-situ experiments were conducted to ground-truth the common seagrass, P. oceanica, in time and space of the Turkish Mediterranean water in 2011-2012 using a scientific echosounder with a split beam transducer operated at a frequency of 206 kHz. After the separation of the seagrass from spurious scatterers, the acoustic parameters (Sa: area backscattering strength, Sv: volume backscattering strength, and TS: Target Strength) were correlated and regressed with the biometric variables (Leaf Area Index, biomass, volume, length, width, diameter, or thickness) of different parts (leaf, rhizome, and sheath) of the seagrass. Estimation of biometrics by acoustic methods has been considered a challenge up to now. Statistical relationships between biometrics and acoustics were precisely examined for the species. The relationships were linearly established in the acoustic geometric region. There was a seasonal difference in the relationships. Their rhizomes and sheaths were considered unstable non-linear parts and remained unexplained for the acoustic response. Acoustic response to the leaf density (d, g cm-3), which was a distinguished component in the reflection, was found to be dependent on the seasonal biological activities of P. oceanica. Posidonia, which has a d greater than 1 g/cm3, produced the geometric region. The present study was the first attempt to establish the relationships of the seagrass under protection, and can decrease usage of destructive methods for future studies.

Biometrical Variation of Posidonia oceanica with Different Bottom Types Along the Entire Turkish Mediterranean Coast - Erhan Mutlu; Güler Sıla Duman; Doğukan Karaca; Yaşar Özvarol; Ahmet Şahin (Ocean Science Journal, 2023)

Seasonality and phenology of an epiphytic calcareous red alga, Hydrolithon boreale, on the leaves of Posidonia oceanica (L) Delile in the Turkish water - Erhan Mutlu; Doğukan Karaca; Güler Sıla Duman; Ahmet Şahin; Yaşar Özvarol; Cansu Olguner (Environmental Science and Pollution Research, 2022)

Population Dynamics and Ecology of Caulerpa Prolifera vs Caulerpa Taxifolia var. Distichophylla within a Levantine Gulf - Erhan Mutlu; Cansu Olguner; Mehmet Gökoğlu; Yaşar Özvarol (Thalassas: An International Journal of Marine Sciences, 2022)

Seasonal Growth Dynamics of Posidonia oceanica in a Pristine Mediterranean Gulf - Erhan Mutlu; Cansu Olguner; Mehmet Gökoğlu; Yaşar Özvarol (Ocean Science Journal, 2022)

Spatiotemporal Density and Ecology of Batoids (Elasmobranchii) Along a Turkish Shelf-upper Slope of the Mediterranean Sea During Years 2009–2015 - Erhan Mutlu; Mehmet Cengiz Deval; Ilaria de Meo; İsmet Saygu; Claudia Miglietta (Thalassas: An International Journal of Marine Sciences, 2022)

Spatiotemporal biometrics of Cymodocea nodosa in a western Turkish Mediterranean coast - Erhan Mutlu; Cansu Olguner; Yaşar Özvarol; Mehmet Gökoğlu (Biologia, 2022)

Comparative trace element trends in Posidonia oceanica and its sediments along the Turkish-Mediterranean Sea coast - Rafet Çağrı Öztürk; Kenan Gedik; Ahmet Şahin; Yaşar Özvarol; Erhan Mutlu (Environmental Science and Pollution Research, 2021)

Spatiotemporal and ecological distribution of megabenthic crustaceans on the shelf-shelf break of Antalya Gulf, the eastern Mediterranean Sea - ANNALISA PATANIA; ERHAN MUTLU (Mediterranean Marine Science, 2021)
The spatiotemporal distribution and ecology of the suprabenthic and benthic mega-crustaceans were studied in the shelf-shelf break of Turkish waters of the eastern Mediterranean Sea (Antalya Gulf). Sampling was conducted seasonally in May 2014, August, October, and February 2015 using an otter trawl at depths of 10, 25, 75, 125 and 200 m along three transects. A total of 59 species were identified comprising 53 decapods (Eumalacostraca: Eucarida), 3 isopods (Eumalacostraca: Peracarida), and 3 stomatopods (Hoplocarida). Eighteen of the total identifiable species were invasive, and some of them significantly influenced the crustacean community structure. Parapenaeus longirostris, Pagurus prideaux, Charybdis (Goniohellenus) longicollis and Medorippe lanata were the most common species. Parasquilla ferussaci was reported for the first time in Turkish water of the Levantine Sea. Community structure showed seasonal patterns and differed along the depth gradient of habitat heterogeneity. The megabenthic crustacean assemblage was driven mainly by seafloor depth and was related to the fishing disturbance in the area (fishing/no-fishing zones). Environmental parameters were measured for each sample and tested in relationship to crustacean abundance by multivariate analysis CCA (canonical correspondence analysis). The results revealed significant differences in community structure related to substrate and the fine fraction of the bioseston.

An intronic variant in BRAT1 creates a cryptic splice site, causing epileptic encephalopathy without prominent rigidity - Fatma Kurt Colak; Naz Guleray; Ebru Azapagasi; Mutlu Uysal Yazıcı; Erhan Aksoy; Nesrin Ceylan (Acta Neurologica Belgica, 2020)

Spatio-temporal distribution of pufferfish (Tetraodontidae) along the Turkish coast of the Mediterranean Sea - ERHAN MUTLU; ILARIA DE MEO; CLAUDIA MIGLIETTA (Mediterranean Marine Science, 2020)
Pufferfish represent a serious threat to the marine ecosystem in the Mediterranean Sea. To better understand the population dynamics of pufferfish and their relation with ecological parameters, six pufferfish species were studied in two fishing and one non-fishing zone in one of the most oligotrophic regions of the Mediterranean Sea during 2014 and 2015, including different habitats of vegetated and non-vegetated and seasons. The results provide information on pufferfish ecological status compared with more eutrophic zones in which these species could potentially worsen their impact. Four species were common in the study area and two were rare. The dominant species was Lagocephalus suezensis, reaching abundances of 11,000 ind/km2 at 25 m in October, followed by Lagocephalus sceleratus, Lagocephalus guentheri, and Torquigener flavimaculosus. The rarest species, Tylerius spinosissimus and Sphoeroides pachygaster, reached higher abundance and biomass in October and February than the other sampling months. The riverine and meadow habitats played a crucial role for nursing and reproduction in the population dynamics of Lagocephalus species, while T. flavimaculosus was absent in these areas. Sex ratios changed depending on season and location. The occurrence of larger individuals of Lagocephalus spp. and T. flavimaculosus at greater depths evidenced an ontogenetic migration. Overall, length-weight (L-W) relationships indicate isometric growth for each of the species studied. Pufferfish populations were primarily a function of habitat and depth of seafloor and secondarily with water productivity.

Ecological distribution of demersal fish species in space and time on the shelf of Antalya Gulf, Turkey - Ilaria de Meo; Claudia Miglietta; Erhan Mutlu; M. Cengiz Deval; Cansu Balaban; M. Tunca Olguner (Marine Biodiversity, 2018)

Some marine leeches and first record of Branchellion torpedinis Savigny, 1822 (Annelida, Hirudinea, Piscicolidae) from elasmobranchs in Turkish waters, with new host records - Nuri Başusta; Ilaria De Meo; Claudia Miglietta; Erhan Mutlu; M. Tunca Olguner; Ahmet Şahin; Cansu Balaban; M. Cengiz Deval; Ummugulsum Usaklı Yurtseven; Analisa Patania (Marine Biodiversity, 2016)

Recent distribution and size structure of gelatinous organisms in the southern Black Sea and their interactions with fish catches - Erhan Mutlu (Marine Biology, 2009)

Diel vertical migration of Sagitta setosa as inferred acoustically in the Black Sea - Erhan Mutlu (Marine Biology, 2006)

A comparison of the contribution of zooplankton and nekton taxa to the near‐surface acoustic structure of three Turkish seas - Erhan Mutlu (Marine Ecology, 2005)
The bioacoustics of upper waters of the Black Sea, the Sea of Marmara, and the Mediterranean Sea were studied in October 1999 with an echosounder with 120 and 200 kHz dual‐beam transducers. Net tows were taken to ground‐truth the acoustic volume backscattering. A forward solution was applied to determine significant scatterers of the three seas with regard to detection limits of the frequencies and background noise measured in each sea. The noise was 4 dB higher in the Sea of Marmara than in the other two seas. 200 kHz data showed significant correlation between measured and calculated volume backscattering strength, and density (biomass and abundance) of the taxa. Large‐sized copepods and chaetognaths in the Black Sea, Aurelia , Beroe , chaetognaths and large‐sized and abundant appendicularians in the Sea of Marmara, and fish larvae in the Mediterranean Sea contributed most to the volume backscattering.